Salmonella sp. em ovos e patos (Cairina moschata) de criações informais - Delfino, Denizard André de Abreu (2016)
The survey was conducted in order to investigate the presence of Salmonella sp. in swabs of cloaca and duck eggs coming from 38 informal breeding sites and 38 markets, and to detect anti-Salmonella Gallinarum and Pullorum antibodies in blood serum of these birds, in the State of Goiás and the Federal Distrito. To determine the productive and sanitary profile of the farms where ducks are raised, we applied 38 questionnaires consisting of 12 closed questions. Through the information obtained by the responses to the questionnaires during the visits, we observed that the farms of the studied regions did not present adequate productive and sanitary management. We collected 324 whole blood samples were used in the test Serological Rapid Agglutination plate (SAR) to detect anti-Salmonella pullorum antibodies. In this test 117/324 (36.1%) blood sera were seropositive. We harvested 324 cloacal swabs from ducks and 912 eggs from 38 farms and 38 markets. The samples were subdivided according to the structure in pools, producing 228 eggshell samples, 228 albumen samples and 228 yolk samples, totaling 684 samples. Cloacal swabs and eggs were analyzed by conventional bacteriology for Salmonella sp. We obtained 38 isolates, 36 from eggs in 36/684 (5.3%), and the serovars were Salmonella Heidelberg, Schwarzengrund, antigenic form O: 9.12, and Salmonella typhimurium, and two isolates from cloaca swabs 02/324 (0.62%). The identified serovars were Salmonella Typhimurium and Hadar. The 36 isolates from eggs and two from cloacal swabs were submitted to susceptibility test to 15 antimicrobials, from which we obtained the following distribution of resistance: 29/38 (76.3%) to sulfonomide, 14/38 (36, 9%) to enroflaxacin, 10/38 (26.3%) to amoxicillin, 7/38 (18.4%) to ampicillin, 7/38 (18.4%) to gentamicin, 6/38 (15.8%) to cotrimoxazole, 6/38 (15.8%) to cephalothin, 6/38 (15.8%) to trimethoprim, 03/38 (7.9%) to ceftiofur, 05/38 (13.1 %) to neomycin, 5/38 (13.1%) to tetracycline, 5/38 (13.1%) to fosfomycin, 3/38 (7.9%) to chloramphenicol, 2/38 (5.3%) to ciprofloxacin, and 0/38 (0%) to florfenicol. The percentage distribution of the isolated serovars was: 32/38 (84.2%) Salmonella Schwarzengrund, 3/38 (7.9%) Salmonella Typhimurium, 1/38 (2.6%) the antigen form: 9.12, 1/38 (2.6%) Salmonella Heidelberg, and 1/38 (2.6%) Salmonella Hadar. The 36 isolates of Salmonella were also submitted to proof of real-time polymerase chain reaction (real-time PCR) on which the following genes were detected: 33/35 (94.3%) for rfbJ, 07/35 (20%) for Int1 gene, and 06/35 (17,1%) for Sul1 gene. Therefore, we verified circulation of Salmonella in ducks and their eggs in informal rearing farms in the state of Goiás and in the Federal District, we also confirmed the antimicrobial resistance and detected resistance genes. This information is important for determining risk for both poultry and public health.